Aftershocks - Kingsley Kent, Susan. author. aut Link
IX, 232 p.
Keywords: Aftershocks studies how meanings of shellshock and imagery presenting the traumatized psyche as shattered contributed to Britons' understandings of their political selves in the 1920s. It connects the force of emotions to the political culture of a decade which saw extraordinary violence against those regarded as 'un-English'.